One day I will write about this place a memoir - Wainaina, Binyavanga (Graywolf Press, 2011)
In this memoir, Wainaina takes us through his school days, his mother's religious period, his failed attempt to study commerce in South Africa, a moving family reunion in Uganda, and his travels around Kenya.